Living with Alligators: A Florida Reality - Elizabeth Swiman; Mark Hostetler; Martin Main; Sarah Webb Miller (EDIS)
Living in Florida, we have to share our space with a very large reptile, the American alligator (Alligator mississipiensis). Because of Florida's booming population growth, people and alligators are constantly forced to cross paths, increasing the chances of conflict. Knowing where alligators live, how they behave, and what you can do to avoid conflict with alligators is key to sharing space safely (Figure 1). This document is WEC 203, one of a series of the Department of Wildlife Ecology and Conservation, UF/IFAS Extension. Original publication date September 2005.